Effect of different extracts and fractions of Senecio biafrae (Oliv. &Hiern) J. Moore on in vivo and in vitro parameters of folliculogenesis in experimental animals. (6th April 2020) - Lienou, L.L.; Telefo, P.B.; Rodrigues, G.Q.; Donfack, J.N.; Araújo, R.A.; Bruno, J.B.; Njimou, J.R.; Mbemya, T.G.; Santos, R.R.; Souza, J.F.; Figueiredo, J.R.; Rodrigues, A.P.R.
Abstract: Background: Senecio biafrae is a medicinal plant widely used in traditional medicine to cure female infertility. Some effects have been pharmacologically demonstrated on immature female rats but in vivo and in vitro investigations are still necessary for determining its mechanism of action. The aim of the present study was to evaluate the estrogenic and FSH-like effects of the plant extracts and fractions on some fertility parameters in immature female rats and on in vitro survival and growth of swine preantral follicles. Methods: 21–23 days old female Wistar rats orally received extracts and fractions of S. biafrae at 0, 8 and 64 mg/kg doses over 20 days. The LH, FSH, estradiol and progesterone serum levels were evaluated as well as the ovarian cholesterol, uterus and ovaries masses and proteins. The numbers of follicles at different developmental stages were recorded in ovarian cortexes after histology. Slices of swine ovarian cortexes were cultured along 1 or 7 days in alpha-minimum essential medium (α-MEM) and fixed for morphological analysis of preantral follicles. The fresh control, cultured control (CIV control) and different Senecio biafrae -treated ovarian fragments were analyzed for preantral follicles development. Treatments that showed the best follicle growth in culture were submitted to AgNOR test. The aqueous and MeOH/CH2 Cl2 extracts as well as the ethyl acetate and hexane fractions of S. biafrae were submitted to the HPLC for analysis of polyphenolic secondary metabolites. Results: Ovarian and uterine proteins were significantly high (p < 0.01) in animals treated with the two dosages of ethyl acetate and n-butanol fractions. The same result was recorded with uterine proteins in animals treated with the hexane fraction. The FSH level significantly dropped with all ethanolic extract doses and with the 64 mg/kg dosage of the methanol/methylene chloride (MeOH/CH2 Cl2 ) extract while LH was reduced (p < 0.01) in almost all the treated groups. Estradiol level was significantly increased (p < 0.001) in the three groups receiving the extracts, but reduced (p < 0.001) in the three groups receiving the fractions of the plant. The progesterone level increased with almost all the treated groups. Primary and secondary follicles augmented (p < 0.01) in MeOH/CH2 Cl2 extract and n-butanol fraction while tertiary follicles increased with the same extract and the ethyl acetate fraction (p < 0.05). Treatments with aqueous and ethanolic extracts as well as ethyl acetate fraction led to a significant increase (p < 0.05) in the number of morphologically normal follicles after 7 days of culture as compared to the CIV control. The number of AgNOR dots per follicle was significantly low (p < 0.05) in all cultured groups as compared to the fresh control, except the ethyl acetate 2.8 ng/ml dosage. The same observation was done with AgNOR dots per cell in the 2.8 ng/ml dosage aqueous extract-treated fragments. The phenolic compounds mainly encountered in the plant, independently of the extract or fraction are apigenin, eugenol and rutin. Conclusion: Extracts and fractions of S. biafrae have an important FSH-like effect which induces follicular survival and growth. Graphical abstract: Image 1